Clinical and genetic spectrum of factor XII deficiency in the Han population of East China - Fei Xu; Langyi Qin; Anqing Zou; Lingling Hou; Mingshan Wang; Bile Chen (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Factor XII (FXII or F12) deficiency is a rare inherited disorder, typically lacking haemorrhagic symptoms. There is limited literature exists on FXII deficiency and mutations within the Chinese population. This study aimed to characterize the spectrum of F12 gene mutations in a Chinese cohort and to investigate the relationship between FXII mutations and clinical phenotypes. Methods Genetic and clinical data from 51 unrelated probands with FXII deficiency, along with their families, were meticulously collected and analysed. Results Genetic analysis revealed that 94.1% of probands carried genetic defects, with 29 mutations pinpointed in the F12 gene. Of these, 18 mutations were previously reported for the first time by our research group, including c.303_304delCA, c.1078G > A, c.1285 C > T, among others. Of the mutations, 17 are missense, constituting 58.6% of the total. Additionally, 11 are deletions or insertions, of which 8 result in frameshifts, while the remaining one is a nonsense mutation. These mutations were predominantly concentrated in two crucial regions: the catalytic domain and the kringle domain. The most frequently observed mutations were c.1681G > A, closely followed by c.1561G > A and c.1078G > A, indicating a dominance among these mutations. Additionally, a prevalent polymorphism at position 46 was observed in the majority of probands, with 47.1% having the 46T/T genotype and 13.7% having the 46 C/T genotype, which may potentially impact FXII activity. The broad spectrum of asymptomatic FXII deficiency observed within the Han population of East China. Conclusions We speculate on the potential impact of recurrent mutations on the efficacy of new drugs being developed to target FXII for thrombosis prevention and treatment. Furthermore, it is important to explore their influence on FXII-related pathways beyond the activation of the contact pathway in the coagulation cascade.